2021
DOI: 10.3390/w13040495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Unsteady Friction Models Used in Engineering Software for Water Hammer Analysis: Implementation Case in WANDA

Abstract: Transient events are frequent in water distribution systems. However, until now, most of the applications based on transient analyses are merely theoretical. Additionally, their implementation to real engineering problems is limited due to several physical phenomena accompanying transient waves, which are not accounted for in the classic approach, such as unsteady friction. This study investigates different unsteady friction models’ performance in terms of accuracy, efficiency, and reliability to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
12
0
7
Order By: Relevance
“…Interestingly, most commercial engineering programs for unsteady pipe flow analysis do not allow unsteady friction to be taken into account. The only model that is available in some programs is the IAB Brunone-Vitkovský model [18]. The purpose of the numerical calculations was to test the suitability of this model for simulating rapid water hammer events in a pipeline system with an internal EPDM hose.…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…Interestingly, most commercial engineering programs for unsteady pipe flow analysis do not allow unsteady friction to be taken into account. The only model that is available in some programs is the IAB Brunone-Vitkovský model [18]. The purpose of the numerical calculations was to test the suitability of this model for simulating rapid water hammer events in a pipeline system with an internal EPDM hose.…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…With respect to viscoelasticity, the Kelvin–Voigt (K–V) model has been used to describe the viscoelastic behavior of the pipe wall [ 7 ]. As for friction, one-dimensional (1D) quasi-steady and unsteady friction models [ 8 , 9 , 10 , 11 ] and two-dimensional friction models [ 12 , 13 , 14 , 15 ] have been used to describe the wall shear stress in transient flows. Generally, the classic transient flow model with a quasi-steady friction model is capable of accurately simulating the maximum value in terms of the pressure fluctuation in elastic pipes; however, it cannot accurately describe the peak pressure damping in most instances [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the viscoelastic model was more accurate when simulating the peak pressure damping than the elastic model. Abdeldayem et al [ 11 ] compared the accuracy of different unsteady fiction models in engineering practice. They concluded that the modified IAB model is relatively suitable for simulating pressure fluctuation in transient flows.…”
Section: Introductionmentioning
confidence: 99%
“…The time increment updated the weight function of the Zielke model. Abdeldayem [16] studied and explored the performance of different unsteady friction models in terms of accuracy, efficiency, and reliability to determine the most suitable model for engineering practice. Through comparison, it was found that Vítkovský's unsteady friction model is the most suitable.…”
Section: Introductionmentioning
confidence: 99%